Changes in perceptions of suburban values in American films from the 1950s to the 1990s = Thay đổi trong quan niệm về giá trị của vùng ngoại ô trong các phim Mỹ từ những năm 1950 cho tới những năm 1990 - Quách, Thị Kiều Oanh (2021)
The aim of this study is to show the changes in perceptions of suburban values in American films from the 1950s to the late 1990s. The study looks at on-screen portrayal of suburban values to see if they match reality. The research subjects are five suburban-centered American films made during that period, ranging from the 1950s to the late 1990s namely, The Man in Gray Flannel Suit (1956), The Graduate (1967), Pleasantville (1998), The Truman Show (1998) and American Beauty (1999). Content analysis is the main data analysis method. The films are analyzed in three main domains: neighborhood, family values, and gender struggles. The findings of this thesis will indicate that the 1950-1960 selected American suburban films are in favor of constructing a bourgeois utopia and promote strict and rigid gender roles at home, at work, and in education. Meanwhile, the selected suburban films from 1990 onwards adjust to changes in the society, shifting to a portrayal of contemporary suburbia. This thesis hopes to be a useful source of reference for students who are interested in American Studies